Financing Sustainable Development : Ideas for Action 2016 - Mohieldin, Mahmoud (2016)
Logistics and supply chains are the wheels of trade, commerce and economic activity around the world. However, in developing economies and emerging markets there are numerous challenges that make access difficult. Most prominent are the lack of standardized addressing systems, and inefficient or inadequate countrywide postal infrastructure that raises the cost of logistics, especially in delivery at the last mile. The authors proposal recommends a low cost peer-to-peer delivery system where senders are connected to local transporters who can carry out scheduled or on-demand deliveries. This system will be executed by means of a technology platform that facilitates this interaction between the different customer segments. There is significant opportunity and potential in establishing this service in emerging economies around the world that face similar problems. Because of the large market opportunity and its significance in the West-African region, Nigeria is the authors target for the solution. The authors plan is to eventually expand this service regionally.